Cow dung-derived engineered biochar for reclaiming phosphate from aqueous solution and its validation as slow-release fertilizer in soil-crop system. (20th January 2018) - Chen, Qincheng; Qin, Jiaolong; Sun, Peng; Cheng, Zhiwen; Shen, Guoqing
Abstract: An effective engineered biochar was investigated by pyrolyzing cow dung for phosphorus (P) adsorption from water solutions and by reusing the biochar as slow-release fertilizer in soil. Response surface methodology (RSM) was employed to optimize the adsorption conditions. Six variables were screened using the Plackett-Burman design. Adsorbent dose, initial P concentration, and pyrolysis temperature were the most important variables. A significant interactive effect was observed between adsorbent dose and initial P concentration. Under the optimized conditions, the adsorption capacity of the engineered biochar reached 345 mg g −1, which was significantly higher than those previously obtained under the same initial P concentrations. The scanning electron microscopy with energy dispersive spectrometry analysis proved the formation of crystals on the surface of the engineered biochar. Results of X-ray diffraction and X-ray photoelectron spectroscopy indicated that P adsorption was controlled by a precipitation mechanism. Amendment of P-laden engineered biochar into the soil planted with lettuce significantly improved soil available P, organic carbon content, soil moisture, and pH. As a result, seed germination, crop growth, crop yields and P concentration of lettuce were promoted. These results suggested that RSM optimization increased the P adsorption capacity of the engineered biochar. Moreover, the P-laden engineered biochar derived from cow dung can be reused as soil amendment to serve as slow-release P fertilizer. Graphical abstract: Image Highlights: A novel engineered cow dung-derived biochar was used to adsorb P in wastewater. The P adsorption conditions on biochar were optimized by RSM. The P adsorption capacity of the engineered biochar increased to 345 mg g −1 . The P-laden biochar as P fertilizer was validated in soil–lettuce system. The amendment of P-laden biochar improved the properties of soil and lettuce.